Analysis on UNIMED Students Understanding in English Learning: Using Communicative Language Teaching Theory - Meisuri, Meisuri; Hudayani, Ardhya; Agnes, Ezra; Anjani, Zahra; Pasaribu, Septian Markus; Sembiring, Posta (Jurnal Akuntansi Hukum dan Edukasi, 2025)
English proficiency is a critical skill for university graduates entering the professional world. However, many Indonesian students struggle with practical English applications due to traditional teaching methods that emphasize grammar rather than real-world communication. This study investigates the effectiveness of Communicative Language Teaching (CLT) in enhancing Unimed students’ understanding of English for professional purposes. A mixed-methods approach, combining qualitative and quantitative data, is employed to assess student progress. The research involves classroom observations, pre- and post-tests, surveys, and interviews with students who receive CLT-based instruction. Findings indicate that CLT significantly improves students' ability to write job-related documents, such as CVs, cover letters, and professional emails, as well as their confidence in workplace communication. The study highlights challenges in implementing CLT, including adaptation difficulties and varying levels of student engagement. Based on the results, recommendations are made to integrate CLT into university curricula to better prepare students for professional communication.